HOSPITAL STAY IN COVID-19 PATIENTS: THE ROLE OF CLINICAL CHARACTERISTICS AND PHYSIOTHERAPY INTERVENTIONS - Souza, Maria da Silva; João , Pereira Santos; Rocha, Ana Oliveira (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in 2020 prompted a global health crisis. COVID-19 can manifest as mild flu-like symptoms or progress to severe respiratory tract infections, with varying degrees of severity. As the pandemic unfolded, the demand for healthcare resources, particularly in terms of hospitalization and intensive care, posed significant challenges. This study seeks to investigate the impact of clinical characteristics and physiotherapeutic interventions on the length of hospital stay in discharged COVID-19 patients. With a growing understanding of the virus and its effects, physiotherapists have become integral members of multidisciplinary teams working to restore lung and motor function, which can be impaired by the inflammatory response to the viral infection. The duration of hospitalization for COVID-19 patients is a crucial metric affecting patient turnover and healthcare system capacity, making it essential to explore the factors that influence it. This study aims to shed light on the role of physiotherapeutic interventions and patient characteristics in this context.